Pembelajaran PAI Berbasis PAIKEMI: Kajian Maudhu’i tentang Air - Sulaiman Sulaiman (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2015)
Learning is a process of educational interaction in the classroom. Works well for learning needs to be supported by various elements, one of the most important element is the learning model used by the teacher will give support to the success. PAIKEMI a learning model that is oriented to chill centered. The Qur'an is a book that is very complete everything has been written in his. Water (ماء) based on the results of the study authors found these words in the Qur'an as much as 56 times. Water favors not only be used as the material necessities of life, but more than that, the water can be taken as a model of learning that is PAIKEMI. The following verses collected interpreted Maudhu'i (thematic) as well as by opening a variety of interpretations, opinions of experts and then analyzed. Based on the nature of the liquid, clear, flowing into the lower and soothing and provide benefits for living things, enrich the soil / revive a dead land and green plants. This illustrates the learning environment should be created as water that continuously provide benefits and favored by many people, as well as learning conditions must be created with pleasant conditions as well as Islamic and delivery of learners critical and creative.